Fragilidade financeira e risco de insolvência de caixa nos governos locais brasileiros - Lira, Aluska Ramos de (2025)
The assessment of the financial health of local governments seeks to avoid the financial risk of operating in a situation of cash insolvency, indicating financial fragility, maintaining sufficient levels of internal financial resources to meet its current obligations and prepare the entity to face unexpected situations arising from the environment. Thus, this thesis had as its general objective to investigate to what extent the risk of cash insolvency, measured by means of Value at Risk (VaR), reflects higher levels of financial fragility in local governments. Thus, this study proposes that the risk of cash insolvency is a critical indicator of financial fragility, signaling maximum potential losses that make municipalities vulnerable to imminent financial crises, especially in Ponzi positions, in which cash flows are insufficient to cover obligations. This thesis had as its preponderant theoretical support Hyman Minsky's theory of financial instability associated with the government's financial condition. The study proposed a risk assessment measure, using an adaptation of the VaR method applied to the public sector. In this sense, by combining two theoretical lenses, a new way of assessing the government's financial condition is proposed, at its highest level of risk, bringing to the theoretical body the vision of the government's financial risk condition. The cash solvency by the level of internal financial resources, measured by the Financial Surplus, was adopted as the variable to assess financial fragility, comprising an analysis of all Brazilian municipalities during the period from 2007 to 2023, totaling a sample of 82,454 observations. The VaR estimate was used via a quantile regression model to test the research hypotheses. Thus, it was possible to observe from the confirmation of H1 that Brazilian municipalities face a high risk of cash insolvency, with substantial potential losses and that financial fragility worsens with the loss of cash solvency as the municipality's VaR increases, as confirmed by H2. Municipalities present varying levels of insolvency risk, with some presenting very high losses, in contrast to others with lower volatility, given the confirmation of H3 that insolvency risk is not uniform among municipalities. In terms of financial fragility classification, it was possible to identify that the most vulnerable ones persisted at different levels of risk. Finally, it was possible to confirm that VaR, in this thesis, proved to be an effective and robust measure to assess the financial fragility of local governments, emerging as a crucial tool capable of identifying and demonstrating significant and imminent financial risks of individual financial crisis of the local government, alerting to the need for preventive interventions. Therefore, this thesis brings relevant contributions by providing a prognosis for effective monitoring of cash insolvency risks of local governments, in order to allow governments to take strategic response measures to mitigate risks before the crisis can set in. Serving as a warning signal for stricter fiscal and financial policies aimed at preventing serious financial crises, by providing an early warning measure for short-term financial difficulties that is easy to use and interpret by planners, policymakers and citizens.